Labor Market Adjustment, Reform and Productivity in Colombia : What are the Factors that Matter? Volume 2 : Technical Report - World Bank (Washington, DC, 2012)
This report carries out a detailed evaluation of the 2002 labor reform in Colombia, and in doing so, it also assesses the performance of the Colombian urban labor market and identifies the main policy challenges faced in this area. The report has three broad goals: First, to provide additional evidence to inform the intense debate taking place in the country around labor market issues, especially the reform. Second, to shed light on the key factors preventing a swift recuperation of the labor market. Third, to offer sensible policy alternatives that complement the step taken with the labor reform and address those key factors. The analyses are carried out for the key labor market outcomes: employment, unemployment, formality and wages, as well as productivity. Through the analysis of these variables the report tries to enhance the understanding of issues such as informality, labor market rigidities, job creation, protection against shocks and private sector performance. By and large, these determine whether people can find gainful employment, be adequately protected against shocks and whether firms are profitable so that, on the one hand, investment and technology adoption take place and, on the other, employment and wages grow, which are the truly important concerns for policy makers. The report illustrates key problems faced by Colombia: slow growth reflecting poor productivity performance, high and persistent unemployment and labor market rigidities that help in keeping unemployment high and productivity low. The 2002 labor reform shows positive results in some areas, while the impact on others was uncertain or moderate. Thus, the country today has three broad challenges. First, making the labor market as efficient as possible; second, increasing productivity growth as a precondition for stronger economic performance, and third, providing effective and inclusive services of social protection for the most vulnerable. These are the channels that will ultimately enable the increase of formal employment and favor wage growth.